Preparation and property studies of new detectors of transuranium elements - Andryushchenko, A.Yu.; Blank, A.B.; Budakovsky, S.V.; Zelenska, O.V.; Shevtsov, M.I. (Functional Materials, 2006)
The possibility to use porous scintillators based on the organic molecular crystal of p-terphenyl for determination of a-nuclides in the environmental water has been shown. The technological methods of the porous scintillator preparation have been improved. As a selective sorbent for transuranium elements, the strong-basic anion-exchange resin VP-
lAp was used. The operation efficiency of the prepared material has been checked using model systems of ²³⁹Pu reference solutions. Показано принципову можливiсть використання пористих сцинтиляторiв на основi органiчного молекулярного кристала n-терфенiлу для визначення a-нуклiдiв у водних об'єктах довкiлля. Удосконалено технологiчнi прийоми виготовлення пористих композитiв. Як селективний до трансуранових елементiв сорбент, використано сильноосновний анiонiт ВП-lап. Дослiдження працездатностi запропонованого матерiалу проведено на модельних системах на основi зразкових радiоактивних розчинiв ²³⁹Pu. Показана возможность применения пористых сцинтилляторов на основе органического молекулярного кристала n-терфенила для определения a-нуклидов в водных объектах окружающей среды. Усовершенствованы технологические приемы изготовления пористых композитов. В качестве селективного к трансурановым элементам сорбента выбран сильноосновный анионит ВП-lап. Исследование работоспособности предлагае мого материала проводилось на модельных системах на основе образцовых радиоактивных растворов ²³⁹Pu.